Frequency of osteoradionecrosis of the lower jaw after radiotherapy of oral cancer patients correlated with dosimetric parameters and other risk factors - Uzun-Lang, Kristin; Held, Thomas; Meixner, Eva; Tonndorf-Martini, Eric; Ristow, Oliver; Moratin, Julius; Bougatf, Nina; Freudlsperger, Christian; Debus, Jürgen; Adeberg, Sebastian (Head & face medicine, 2022)
Osteoradionecrosis (ORN) of the lower jaw is a serious late complication after radiotherapy in patients with oral cavity cancer. The aim of this study is to generate more insight into which patient- and treatment-related factors are associated with the development of ORN in oral cavity cancer patients undergoing postoperative radiotherapy.
Gesehen am 02.06.2022